If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -2) + 4 = -11 Reorder the terms: 5(-2 + x) + 4 = -11 (-2 * 5 + x * 5) + 4 = -11 (-10 + 5x) + 4 = -11 Reorder the terms: -10 + 4 + 5x = -11 Combine like terms: -10 + 4 = -6 -6 + 5x = -11 Solving -6 + 5x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 5x = -11 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = -11 + 6 5x = -11 + 6 Combine like terms: -11 + 6 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 6+4(-4)= | | t^3-9t=0 | | 12h-10=42 | | 4(2x+3)=46 | | (3x+5)=3 | | (2x-5)(x+3)=(x-2)(2x+1) | | 12+(h+10)=42 | | 5(x+4)-x=0 | | 7+2x=5-4x | | (-2)[9+(-5)]= | | 3x+4=8-(6x-9) | | 7-5(5-7x)=0 | | (-2)(4)+5[6-(-2)]= | | 28=0.5*0.8*r^2 | | 5a-3(a+1)=-5 | | 16=0.5x | | 3w-10w-3+2=20 | | 47=7x+6(-1x+6) | | -48=4x+3(-4x+8) | | 74=3x+2(6x-8) | | 81=-2x-3(5x+7) | | x^2-36a^2+20x+100=0 | | -110=-2x+7(3x+6) | | 3(2x-1)-2=2(x+9)+1 | | x^2-16y^3=0 | | 23*3=23 | | 35+8x=7x+3 | | 2x(3x-4)+5=3x(2x-5)-4 | | 3a-2=2-2a+1 | | h=-16t^2+8t+80 | | H(t)=16t^2+144 | | -4x^2+22x+42=0 |